Доцільність комплексного підходу до використання імуногістохімічних досліджень у діагностиці пухлин - Туффаха, М.; Гичка, С. Г.; Шмідт-Шнайдерс, Д. (Clinical Endocrinology and Endocrine Surgery, 2016)
The paper conducted a comprehensive histological, immunohistochemical and molecular genetic study of biopsy and surgical specimens case from practice – neoplastic lesions of the thyroid gland in order to justify the algorithm morphological diagnosis and differential diagnosis pathologists at this kind. Argued that with the immunohistochemical diagnosis of thyroid neoplasia should be used full panel of antibodies that includes thyroglobulin, TTF-1, PAX-8, calcitonin, cytokeratin profile. In case of any deviation from the standard results of immunohistochemical reactions characteristic of thyroid tumors, it is necessary to conduct a differential diagnosis with the use of an additional panel of antibodies.